Sex differences in the role of phospholipase A2-dependent arachidonic acid pathway in the perivascular adipose tissue function in pigs - Ahmad, Abdulla A.; Randall, Michael D.; Roberts, Richard E. (Wiley, 2017)
Previous studies have demonstrated that perivascular adipose tissue (PVAT) causes vasoconstriction. In this present study, we determined the role of cyclooxygenase-derived prostanoids in this contractile response and determined whether there were any sex differences in the regulation of vascular tone by PVAT. Contractions in isolated segments of coronary arteries were determined using isolated tissue baths and isometric tension recording. Segments were initially cleaned of PVAT, which was then re-added to the tissue bath and changes in tone measured over 1 hour. Levels of PGF2α and thromboxane B2 (TXB2) were quantified by ELISA and PGF2α (FP) and thromboxane A2 (TP) receptor expression determined by Western blotting. In arteries from both male and female pigs, re-addition of PVAT caused a contraction, which was partially inhibited by the cyclooxygenase inhibitors indomethacin and flurbiprofen. The FP receptor antagonist AL8810 attenuated the PVAT-induced contraction in arteries from males, whereas the TP receptor antagonist GR32191B inhibited the PVAT-induced contraction in arteries from females. Although there was no difference in PGF2α levels in PVAT between females and males, PGF2α produced a larger contraction in arteries from males, correlating with a higher FP receptor expression. In contrast, release of TXB2 from PVAT from females was greater than from males, but there was no difference in the contraction by the TXA2 agonist U46619, or TP receptor expression in arteries from different sexes. These findings demonstrate clear sex differences in PVAT function in which PGF2α and TXA2 antagonists can inhibit the PVAT-induced vasoconstriction in male and female PCAs, respectively.